2020
DOI: 10.1111/jgh.14912
|View full text |Cite|
|
Sign up to set email alerts
|

DRP1 upregulation promotes pancreatic cancer growth and metastasis through increased aerobic glycolysis

Abstract: Background: Mitochondrial shape is dynamically changed by fusion and fission processes in cells, and dysfunction of this process has become one of the emerging hallmarks of cancer. However, the expression patterns and biological effects of mitochondrial fission and fusion proteins in pancreatic cancer (PC) are still unclear. Methods: The expressions of mitochondrial fission and fusion proteins were first evaluated by quantitative reverse transcription polymerase chain reaction and western blot analysis in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…Purine metabolism was most affected by indirectly inducing fusion with knockout of Drp1 (Impact = 0.22, Percent Affected = 15.2%); though, still moderately altered via direct fusion with Tet-On Mfn2 (Impact = 0.14, Percent Affected = 10.6%) and pharmacologic fusion with Leflunomide (Impact = 0.10, Percent Affected = 9.1%, Table 5). Both carbohydrate metabolism sub-pathways, PPP, and glycolysis were modestly impacted across the three groups, but knockdown of Drp1 in particular had more impact on glycolysis/gluconeogenesis (Impact = 0.11, Percent Affected = 11.5%), supporting recent findings that Drp1 promotes metabolic changes through glycolysis to drive PDAC tumorigenesis (Table 5) [7,15]. The main pathway that had an impact greater than 0.28 across the Tet-On Mfn2, sgDrp1, and Leflunomide groups was alanine, aspartate, and glutamate metabolism with more than 21.4% of the pathway appearing significantly altered (Table 5).…”
Section: Resultssupporting
confidence: 81%
“…Purine metabolism was most affected by indirectly inducing fusion with knockout of Drp1 (Impact = 0.22, Percent Affected = 15.2%); though, still moderately altered via direct fusion with Tet-On Mfn2 (Impact = 0.14, Percent Affected = 10.6%) and pharmacologic fusion with Leflunomide (Impact = 0.10, Percent Affected = 9.1%, Table 5). Both carbohydrate metabolism sub-pathways, PPP, and glycolysis were modestly impacted across the three groups, but knockdown of Drp1 in particular had more impact on glycolysis/gluconeogenesis (Impact = 0.11, Percent Affected = 11.5%), supporting recent findings that Drp1 promotes metabolic changes through glycolysis to drive PDAC tumorigenesis (Table 5) [7,15]. The main pathway that had an impact greater than 0.28 across the Tet-On Mfn2, sgDrp1, and Leflunomide groups was alanine, aspartate, and glutamate metabolism with more than 21.4% of the pathway appearing significantly altered (Table 5).…”
Section: Resultssupporting
confidence: 81%
“…Purine metabolism was most affected by indirectly inducing fusion with knockout of Drp1 (Impact = 0.22, Percent Affected = 15.2%); though, still moderately altered via direct fusion with Tet-On Mfn2 (Impact = 0.14, Percent Affected = 10.6%) and pharmacologic fusion with leflunomide (Impact = 0.10, Percent Affected = 9.1%, Table 5 ). Both carbohydrate metabolism sub-pathways, PPP and glycolysis, were modestly impacted across the three groups, but knockdown of Drp1 in particular had more impact on glycolysis/gluconeogenesis (Impact = 0.11, Percent Affected = 11.5%), supporting recent findings that Drp1 promotes metabolic changes through glycolysis to drive PDAC tumorigenesis ( Table 5 ) [ 7 , 18 ]. The main pathway that had an impact greater than 0.28 across the Tet-On Mfn2, sgDrp1, and Leflunomide groups was alanine, aspartate, and glutamate metabolism with more than 21.4% of the pathway appearing significantly altered ( Table 5 ).…”
Section: Resultssupporting
confidence: 80%
“… 35 In addition, Liang et al demonstrated that DRP1 was upregulated in pancreatic cancer and let to more mitochondrial fission and enhanced aerobic glycolysis, which resulting in cancer cell growth and metastasis. 36 In the present study, we identified that DRP1 -rs879255689 was related to elevated risk of lung cancer. Rs879255689 is a missense variant and led to Gly379Lys, therefore, we speculated that this variant may change the mitochondrial fission and dynamics of lung cancer patients and participant in the development of the disease.…”
Section: Discussionmentioning
confidence: 50%